MAHAKAM ULU FIVE MONTHS ZERO COVID-19 CASES: WHAT IS THE POLICY OF THE MAHAKAM ULU REGENCY GOVERNMENT IN HANDLING COVID-19? - Budiman Budiman; Jauchar Berlian; Adam Idris; Muhammad Jamal Amin; Rezky Rizandy (DIA: Jurnal Administrasi Publik, 2022)
This study aims to see how the policies carried out by the Mahakam Ulu Regency Government in handling Covid-19. This is based on the fact that in the midst of the widespread spread of Covid-19 cases in East Kalimantan, Mahakam Ulu Regency was able to maintain a status of zero cases from March to early August 2020. Furthermore, this research is a qualitative study. Primary and secondary data are used as data sources in this study. This study uses a purposive sample approach to select sources to determine informants. There were two informants in this study including the Head of the Department of Health, Population Control and Family Planning of Mahakam Ulu Regency who also served as the Covid-19 Rapid Response Team (first informant) and Chairman of Commission III of the Mahakam Ulu Regency DPRD (second informant). The results of the study stated that temporary opening and closing access was carried out with a period of 2 weeks open and 2 weeks closed. Furthermore, in the closed situation, travelers are not allowed to enter except with special permission from the Regent of Mahakam Ulu Regency and during the opening period for travelers who want to enter Mahakam Ulu Regency, they must first fill out SIMAS (Entry Permit) through the Task Force Team and follow the requirements- other requirements such as PCR or Antigen Swab Test according to the decision of the Task Force Team.